"Coś jest ze światem nie tak". Mowa noblowska Olgi Tokarczuk w perspektywie ekolingwistyki zaangażowanej, czyli o wartościach i antywartościach w kontekście zachowania życia na Ziemi = "There is something wrong with the world". Nobel lecture by Olga Tokarczuk in the perspective of engaged ecolinguistics or about values and anti-values in the context of preserving life on Earth - Steciąg, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to trace the Nobel lecture by Olga Tokarczuk in accordance with the assumptions of engaged ecolinguistics, which requires combining critical reflection with creative action to overcome the ecological crisis.
Keywords: Tokarczuk, Olga (1962- ); ekolingwistyka zaangażowana; przemowa noblowska; wartości; antywartość; engaged ecolinguistics; Nobel lecture; values; antivalue